Pengaruh Keaktifan Mengikuti Organisasi Siswa Intra Sekolah (OSIS) Terhadap Hasil Belajar Pendidikan Agama Islam (PAI) di Bengkulu - Pasmah Chandra; Wilda Tri Kartika (STAI Bumi Silampari, 2021)
This study aims to determine the effect of active participation in the Intra School Student Organization (OSIS) on student learning outcomes in the subject of Islamic Religious Education at SMA Negeri 09 Bengkulu City. This type of research is a quantitative study with an associative quantitative approach. Test the validity of the instrument using SPSS16 with Product Moment Correlation and reliability also using SPSS16 with Cronbach's Alpha. The results showed that the activeness of intra-school organizations had an effect on student learning outcomes. This is evidenced by the t count of 2.981 while the t table of 2.064 at the significant level of 0.05. Based on these results t count is greater than t table. So it can be concluded that Ha is accepted and Ho is rejected so that there is an effect of active participation of intra-school organizations on student learning outcomes by 4% while the remaining 96% is influenced by other factors not examined in this study. This can be seen from the value of R Square.